PEMANFAATAN BIJI KETAPANG (Terminalia catappa) SEBAGAI SUMBER PROTEIN DAN SERAT PADA PRODUK MAKANAN STIK - Darmawan, Eman (AGROTECH : JURNAL ILMIAH TEKNOLOGI PERTANIAN, 2016)
The purpose of this study was to determine the effect of substitution ketapan seed to chemical and organoleptic properties of Â the resulted snack food, knowing the exact level of substitution, so obtain the snack food liked the panelists. The design used in this study was completely randomized design (CRD) with single factor that influences the concentration of seed flour substitution ketapan seed consisting of 5 treatments. Each treatment be repeated 3 times. The data obtained was analyzed by Analysis of Variance (ANOVA), if there was a difference between the treatment of advanced test conducted by Duncan`s Multiple Ranges Test Method (DMRT) at the level of 5%. Substitution of wheat flour with ketapan seed flour Â affects the snack food produced, which can reduce the water content of the snack food and increase levels of protein and fiber snack food. Ketapan seed flour substitution preferred by the panelists was substitution ketapan seed flour up to 30% with a value of 3.52 and the criteria snack food produced had a water content of 3.67%, 15.10% db protein content, fiber content of 3.64 % db, brownish yellow color (2.95), a rather tasted wheat flour (3.35), and crispy (3.60).